The Effect of Facilities and Infrastructure Management and Learning Facility Completeness on Student Loyalty with Student Satisfaction as a Mediating Variable. - Ocvan Pandu Kurniawan; Daniel Kurniawan; Eric Harianto (LP2M IAIN Palopo, 2026)
The abstract contains a brief description of the Purpose: This study investigates the effect of facilities and infrastructure management and the completeness of learning facilities on student loyalty, with student satisfaction as a mediating variable based on Expectation Disconfirmation Theory. Methods: A quantitative explanatory survey was conducted involving 80 students of a private junior high school in Samarinda, Indonesia, selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results: The findings show that facilities and infrastructure management and learning facilities significantly influence student satisfaction, while student satisfaction has a strong effect on student loyalty. The direct effects of facilities and learning facilities on loyalty are not significant, indicating that student satisfaction fully mediates these relationships. Implications: The study highlights that student loyalty is formed through satisfaction rather than direct facility provision, suggesting that schools should focus on improving students’ perceived satisfaction through effective facility management and utilization.